1994
DOI: 10.1111/j.2044-8295.1994.tb02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of visual interference with visuospatial working memory

Abstract: Recent discussions of visuospatial working memory have suggested that this subsystem may incorporate a visual buffer which holds visuospatial information relatively passively. Empirical investigations of visual interference with information held within a visuospatial subsystem have yielded somewhat equivocal results. Nonetheless, evidence from Logie (1986) has indicated that visuospatial processing can be disrupted by passive exposure to irrelevant visual material in a manner analogous to the disruption of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
(46 reference statements)
2
25
1
1
Order By: Relevance
“…Thus, the spatial representation affected memory for the verbal material (i.e., the verbal representation). These findings provide strong support for the interdependence of the spatial and the verbal memory processes, as had been suggested by the work of McNamara and LeSueur (1989); the findings are not consistent with the notion that spatial and verbal WM processes are completely independent, as had been suggested by some previous investigations of WM (Friedman & Miyake, 2000;Shah & Miyake, 1996;Toms et al, 1994).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Thus, the spatial representation affected memory for the verbal material (i.e., the verbal representation). These findings provide strong support for the interdependence of the spatial and the verbal memory processes, as had been suggested by the work of McNamara and LeSueur (1989); the findings are not consistent with the notion that spatial and verbal WM processes are completely independent, as had been suggested by some previous investigations of WM (Friedman & Miyake, 2000;Shah & Miyake, 1996;Toms et al, 1994).…”
Section: Discussioncontrasting
confidence: 50%
“…Shah and Miyake (1996) offered evidence to support the separation of spatial thinking and language processes in WM. Similarly, Toms, Morris, and Foley (1994) supported the separation of visuospatial and verbal WM processes. More recently, Friedman and Miyake (2000) argued that spatial and causal dimensions of mental representations are handled independently in different WM subsystems.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…As for visual memory, under some circumstances behaviorallyirrelevant visual inputs seem to enjoy automatic, obligatory entry to visual memory, which allows behaviorally-irrelevant visual material to interfere with retrieval for task-relevant information. Such interference has been seen in visual memory for various spatial attributes, such as the distance separating dots (Hole, 1996) and the locations of cells in twodimensional matrices (Toms, Morris, & Foley, 1994;Washburn & Astur, 1998). However, other studies suggest that interference is not inevitable, but depends upon the stimulus dimension and task details (for example, Lalonde & Chaudhuri, 2002;Ostendorf, Finke, & Ploner, 2004).…”
mentioning
confidence: 98%
“…The use of irrelevant pictures has suggested that perceived inputs have direct and obligatory access to the system, causing detrimental effects on short-term recall and recognition for visuo-spatial material, analogous to the irrelevant speech effect on the phonological loop (Logie, 1986;Logie & Marchetti, 1991;Toms, Morris, & Foley, 1994). Quinn and McConnell explored the effects of passive visual interference with the dynamic visual noise (DVN) task, consisting of a matrix of dots turning black and white randomly, similar to television static, which the subject had to watch but otherwise ignore (McConnell & Quinn, 2000Quinn & McConnell, 1996;.…”
mentioning
confidence: 99%